Folate-mediated macromolecule delivery across the epithelium - Moradi, Emilia (2012)
Folate uses the natural endocytosis pathway via the folate receptor (FR) to enter the cells. Folate conjugation to small or macromolecular therapeutics has hence been exploited for intracellular delivery to, particularly, cancerous cells. This work reports on the expression and functionality of FR in polarised cell monolayer models of respiratory and gastrointestinal mucosa with the view to assess its potential for delivery of folate-modified macromolecular therapeutics either intracellularly or across the epithelium. Four cell lines representing bronchial and intestinal epithelium; cancer-derived intestinal Caco-2 and bronchial cell line Calu-3, and noncancerous intestinal and bronchial cell lines IEC-6 and HBEC were cultured on permeable membranes to produce polarised monolayers. Expression of FR was confirmed by RT-PCR and Western blot analysis for all the tested cell types and shown to be dependent on culturing time. The functionality of the receptor for endocytosis was demonstrated by a model macromolecular folate conjugate (fluorescent ovalbumin-folate (OVA-FA)), whereby significantly higher cellular uptake of the folate-conjugate, relative to non-folate control, was clearly demonstrated. Importantly the data showed that the expressed folate receptor was capable of mediating transport of the macromolecular folate conjugate across (transcytosis) the cells in the polarised monolayers.